Cartilage Oligomeric Matrix Protein–Derived Peptides Secreted by Cartilage Do Not Induce Responses Commonly Observed during Osteoarthritis. (December 2021) - Andrés Sastre, Enrique; Zaucke, Frank; Witte-Bouma, Janneke; van Osch, Gerjo J.V.M; Farrell, Eric
Objective: To evaluate if 3 peptides derived from the cartilage oligomeric matrix protein (COMP), which wounded zones of cartilage secrete into synovial fluid, possess biological activity and might therefore be involved in the regulation of specific aspects of joint regeneration. Methods: The 3 peptides were produced by chemical synthesis and then tested in vitro for known functions of the COMP C-terminal domain from which they derive, and which are involved in osteoarthritis: transforming growth factor-β (TGF-β) signaling, vascular homeostasis, and inflammation. Results . None of the peptides affected the gene expression of COMP in osteochondral progenitor cells ( P > 0.05). We observed no effects on the vascularization potential of endothelial cells ( P > 0.05). In cultured synovium explants, no differences on the expression of catabolic enzymes or proinflammatory cytokines were found when peptides were added ( P > 0.05). Discussion and Conclusions: The 3 peptides tested do not regulate TGF-β signaling, angiogenesis and vascular tube formation, or synovial inflammation in vitro and therefore most likely do not play a major role in the disease process.